Gender and Culturally Responsive School Leadership: Principals’ Practices in Florida’s Elementary Schools - Jones, Nickitra D.; Elmahdy, Sherin Y.; Aly, Ezzeldin R. (European Scientific Journal, ESJ, 2026)
Public school leaders face increasing challenges as student populations become more diverse, and persistent achievement gaps disproportionately affect students of color. Culturally responsive pedagogy (CRP) and leadership have been identified as essential frameworks for addressing these inequities (Gay, 2010). This quantitative study examined the practices of cultural responsiveness among 66 elementary school principals in Florida’s Panhandle, with specific attention to differences based on their gender. Data were collected post–COVID-19 using a demographic survey and the Culturally Responsive Principals’ Rating Scale (CRPRS), which measures five domains: school morale, time and pulse, ethics of bonding, building relationships, ethics of caring, and teacher effectiveness. Descriptive statistics and Chi-square tests of independence were used to analyze principals’ responses. Findings revealed no statistically significant differences in principals’ perceptions and practices of cultural responsiveness based on gender. However, statistically significant differences emerged in the areas of ethical practices, relationship building, and leadership effectiveness. Results suggest that culturally responsive school leadership is less dependent on demographic characteristics and more strongly associated with principals’ ethical decision-making, relational leadership, and capacity to foster inclusive school environments. Implications highlight the importance of intentional relationship building, community engagement, and sustained efforts to create culturally responsive school climates.